Development and validation of a questionnaire measuring factors associated with physical activity in adolescents Desenvolvimento e validação de um questionário para mensurar fatores associados à atividade física em adolescentes - José Cazuza de Farias Júnior; Adair da Silva Lopes; Rodrigo Siqueira Reis; Juarez Vieira do Nascimento; Adriano Ferreti Borgatto; Pedro Curi Hallal (Instituto Materno Infantil de Pernambuco, 2011)
OBJECTIVES: to develop a questionnaire to measure factors associated with physical activity (PA) in adolescents and analyze its reliability and validity. METHODS: a total of 248 adolescents from 14 to 19 years old took part in this study. The factors associated with PA measured were: attitude, self-efficacy, social support of PA and perceived environment. Cronbach's alpha (α) and intraclass correlation coefficients (ICC) were used to test reliability, and exploratory factor analysis to evaluate validity. RESULTS: attitude was measured as a single factor (attitude: α=0.76, ICC=0.89); self-efficacy consisted of two factors: resources for PA (α=0.76, ICC=0.75) and social support and motives for engaging in PA (α=0.76, ICC=0.67); social support was measured as two factors: support for PA from friends (α=0.90, ICC=0.89) and support for PA from parents (α= 0.81, ICC=0.91); and the environment was measured as three factors: access to and attractiveness of places to engage in PA (α=0.69, ICC=0.82), security/safety when engaging in PA (α=0.73, ICC=0.67), and general infrastructure of the neighborhood (α=0.70, ICC=0.75). CONCLUSIONS: the questionnaire exhibited satisfactory validity and reliability and can be recommended for studies investigating adolescents. OBJETIVOS: desenvolver e analisar a fidedignidade e validade de um questionário para mensurar fatores associados à atividade física (AF) em adolescentes. MÉTODOS: participaram do estudo 248 adolescentes de 14 a 19 anos de idade. Os fatores associados à AF mensurados foram: atitude, autoeficácia, apoio social dos pais e dos amigos para prática de AF, ambiente percebido. O alpha de Cronbach (α) e a correlação intraclasse (CCI) foram utilizados para verificar a fidedignidade, e a análise fatorial exploratória para avaliar a validade do questionário. RESULTADOS: a medida de atitude continha um único fator (atitude: α=0,76; CCI=0,89); a de autoeficácia dois fatores: recursos para prática de AF (α=0,76; CCI=0,75), apoio social e motivos para prática de AF (α=0,75; CCI=0,67); a de apoio social dois fatores: apoio dos amigos (α=0,90; CCI=0,89) e dos pais (α=0,81; CCI=0,91); a medida de ambiente três fatores: acesso e atratividade dos locais para prática de AF (α=0,69; CCI=0,82), segurança para a prática de AF (α=0,70; CCI=0,75) e infra-estrutura geral do bairro (α=0,73; CCI=0,67). CONCLUSÃO: o questionário demonstrou validade e fidedignidade (consistência interna e reprodutibilidade) satisfatórias, recomendando a sua utilização em adolescentes.